Memaknai Kuliner Lokal Berbasis Kearifan Lokal dan Technopreneurship Sebagai Daya Tarik Wisata Desa Nongkosawit Gunungpati Semarang - Krisnatalia, Heni; Hendrajaya, Hendrajaya (Journal of Dedicators Community, 2025)
In a world where modernization and changing food habits are happening quickly, traditional cooking styles are often overlooked, even though they represent a valuable mix of skills, culture, history, and national identity. To tackle this issue, the Community Service Team at STIEPARI Semarang started a program designed to learn about, protect, and celebrate the wisdom found in traditional cooking methods. This initiative aimed to boost the abilities of local food entrepreneurs through training, guidance, and online marketing, involving small culinary businesses in the Semarang area using a collaborative method. The outcomes revealed that 80% of those involved became more aware of the significance of culinary heritage as a special feature for marketing, while 75% improved their skills in digital marketing, especially in using social media to advertise their products. The program also created digital marketing materials, such as videos and online catalogs, which the participants have utilized to access broader markets. This effort is anticipated to aid the longevity of local food enterprises while reinforcing the cultural identity of the region